Disease progression and antiretroviral therapy in newly seropositive HIV subjects in a tertiary care hospital in North India - Sanjim Chadha; Preena Bhalla; Arun Kumar Jha; Hitender Gautam; Sanjeev Saini; S. Anuradha; Richa Dewan (Journal of Infection in Developing Countries)
Introduction: In developing countries the standard methods used to monitor HIV disease progression and therapy response are clinical assessment, CD4+ T lymphocyte count measurement, and plasma viral load (PVL) quantification. These tests require expensive equipment and skilled technicians, so monitoring HIV in resource-limited countries remains challenging as few laboratories can offer these tests free of cost.